The new concept of biota protection oin the Republic of Moldova. The Red Data Book of Moldova (2015) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The new concept of biota protection oin the Republic of Moldova. The Red Data Book of Moldova (2015)